2019
DOI: 10.1111/ejn.14543
|View full text |Cite
|
Sign up to set email alerts
|

Shift in lateralization during illusory self‐motion: EEG responses to visual flicker at 10 Hz and frequency‐specific modulation by tACS

Abstract: Self-motion perception is a key aspect of higher vestibular processing, suggested to rely upon hemispheric lateralization and alpha-band oscillations. The first aim of this study was to test for any lateralization in the EEG alpha band during the illusory sense of self-movement (vection) induced by large optic flow stimuli. Visual stimuli flickered at alpha frequency (approx. 10 Hz) in order to produce steady state visually evoked potentials (SSVEPs), a robust EEG measure which allows probing the frequency-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…Further work could also explore different frequencies, stimulation waveforms or orientations. Animal studies have shown that the firing rate of neurons increases with a steeper temporal change ( Fröhlich and McCormick, 2010 ) and several human studies have investigated the effects of stimulation waveforms on brain oscillations ( Dowsett et al, 2020 ; Dowsett and Herrmann, 2016 ) showing that different waveforms differentially modulate brain oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Further work could also explore different frequencies, stimulation waveforms or orientations. Animal studies have shown that the firing rate of neurons increases with a steeper temporal change ( Fröhlich and McCormick, 2010 ) and several human studies have investigated the effects of stimulation waveforms on brain oscillations ( Dowsett et al, 2020 ; Dowsett and Herrmann, 2016 ) showing that different waveforms differentially modulate brain oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…EEG recordings synchronized with participants' perceptual states were obtained in order to accurately distinguish between periods of object-and self-motion. Given that alpha oscillations have been linked to vection [29][30][31] and associated with bistable perception [32][33][34], the EEG analyses focused primarily on alpha band activity and on potential differences in this band between left and right handers.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by tDCS, future cortical studies can be planned with alternating current (AC) stimulation [41] to see if AC stimulation could achieve better inhibitory effect. This is because the brain neurons have oscillatory nature (e.g., the commonly-known brain wave electroencephalogram), therefore we surmise that the AC stimulation that has an antiphase with neurons oscillation may indeed follow a better pattern of results than tDCS.…”
Section: Future Studies 1) Better Inhibition On Cortical Areasmentioning
confidence: 99%